2022
DOI: 10.3390/ijerph191811543
|View full text |Cite
|
Sign up to set email alerts
|

Interventions by Caregivers to Promote Motor Development in Young Children, the Caregivers’ Attitudes and Benefits Hereof: A Scoping Review

Abstract: In the first year of life, the child’s caregivers, including parents and daycare staff, play an essential role, as they are responsible for implementing daily activities to promote the motor development of young children. However, what does the research show about interventions to promote the motor development of 0–36-month-olds carried out by the child’s caregivers, and what are the caregivers’ experiences and attitudes hereof? This scoping review aims to provide an overview of the published studies to derive… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(10 citation statements)
references
References 46 publications
0
2
0
Order By: Relevance
“…The improvements in gross motor skills among children in the intervention groups can be attributed to one of the prominent foci of ¡Míranos! to develop children's gross motor skills via teacher-led structured physical activities [35], which involved modifications of center policy on structured physical activity and staff training on gross motor development as well as provision of lessons and play equipment designed to teach gross motor skills (see Table 1) [53,54]. Previous center-based interventions promoting physical activities and teacher-led activities have reported similar favorable impacts on gross motor development in young children in a childcare setting [52,[55][56][57].…”
Section: Discussionmentioning
confidence: 99%
“…The improvements in gross motor skills among children in the intervention groups can be attributed to one of the prominent foci of ¡Míranos! to develop children's gross motor skills via teacher-led structured physical activities [35], which involved modifications of center policy on structured physical activity and staff training on gross motor development as well as provision of lessons and play equipment designed to teach gross motor skills (see Table 1) [53,54]. Previous center-based interventions promoting physical activities and teacher-led activities have reported similar favorable impacts on gross motor development in young children in a childcare setting [52,[55][56][57].…”
Section: Discussionmentioning
confidence: 99%
“…Among these, authoritative parenting type is a balanced one, in which parent develops a close, nurturing relationship with their children, and children are confident, responsible, and able to self-regulate as they grown ( 35 ). Irrespective of parenting type, caregivers, either parents or grandparents play a vital role in supporting and promoting the motor development in children from an early age ( 14 , 36 ). Previous studies identified the differences in FMS proficiency between boys and girls, which might be due to their behavioral habits, biological or social factors ( 37 , 38 ).…”
Section: Introductionmentioning
confidence: 99%
“…Motor development such as rolling, sitting, crawling, and walking are essential for children's early development and affects many aspects of health [1]. According to the definition from the World Health Organization, WHO, early development refers to the cognitive, physical, language, motor, social, and emotional development in children between 0 and 8 years of age [2].…”
Section: Introductionmentioning
confidence: 99%
“…n1 = number of children, % 2 = percent, GMFCS 3 = Gross Motor Function Classification System, GMFM-66 4 = Gross Motor Function Measure 66.…”
mentioning
confidence: 99%